The effects of presenting different types of vocabulary clusters on very young learners' foreign language learning - KARABULUT, ASLIHAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
The main aim of this study was to find out which type of vocabulary cluster - semantic, thematic and unrelated - very young learners benefit from the most while learning foreign language vocabulary. The study also aimed at shedding light on the effects of these three vocabulary clusters on the immediate and delayed recall of foreign language vocabulary. In accordance with the aims, 51 very young English as a Foreign Language learners participated in the study. A pre-test was administered to determine the target words in the three clusters so that all target words were new to all participants. The participants received immediate recall tests immediately after the instruction of L2 words in each cluster. Delayed recall tests were also administered for each cluster after three days of reviews of the words in the clusters The analysis of the quantitative data results of the study revealed that the presenting L2 words in different type of clusters have a significant effect on very young EFL learners' L2 vocabulary retention, and the subjects remembered significantly more L2 words when the words were grouped in unrelated clusters.
Keywords: very young learners; vocabulary teaching; clusters; retention; recall; DISTINCTIVENESS; MEMORY